The Influence of Third-Party Funds and Financing on the Operational Profit of Bank Bukopin Sharia for the Period 2014-2022 - Aprilia, Yohana; Maika, Ruslianor (MALIA: Jurnal Ekonomi Islam, 2023)
Third Party Funds and Financing are important indicators for Bank Bukopin Syariah, both indicators indicate sustainable activity. Because of this, it is considered a source of income for Bank Bukopin Syariah. This study aims to analyze the impact of external funding and financing on Bank Syariah Bukopin's operational profit from 2014 to 2022. Monthly financial statements are analyzed using quantitative descriptive approaches. In this study, we utilize linear regression to examine standard assumptions about operating profit (Y), financing (X2), and third-party funding (X1). The study found that Third Party Funds on Operating Profit had a significance value of 0.019 (<0.05), whereas Financing on Operating Profit had a significance value of 0.003 (<0.05). Financial backing from outside sources has a substantial impact on operational profit at Bank Bukopin Syariah.